Heavy Metals Contamination in Soil and Vegetables in the Sekenke Gold Mine: Levels, Transfer and Potential Human Health Risk Analysis - Roman, Priscus; Saria, Josephat (NPRC Journal of Multidisciplinary Research, 2025)
Background: The main goal of this study is to evaluate the potential human health risks associated with consuming vegetables contaminated by heavy metals at Sekenke gold mine. Methodology: Five heavy metals (Pb, Cd, Fe, Zn and Cr) were analyzed in soil and in green leafy vegetables (Amaranthus sp and cucurbita moschata) by XRF Rigaku Nex CG instrument, while Arsenic was examined by Atomic Absorption spectrometry (AAS) equipped with a continuous flow of Vapour Generation Accessory (VGA). Results: The average heavy metal concentrations in soils sample with mean average concentrations ± standard error (mg/kg) 204.646 ± 28.671 for Fe, 163.116 ± 16.658 for Cr. 52.403 ± 15.806 for Zn, 23.392 ± 18.049 for Pb, 21.331 ± 7.503 for As and 3.018 ± 0.842 for Cd. In GLV was observed that the average concentrations of As, Pb, Cd and Zn exceeded the maximum acceptable limit by FAO/WHO (2001) while Fe and Cr concentrations are lower than maximum acceptable limits. On average, Amaranthus species can contribute between 1.04% (Fe) to 7.15% (As) of the recommended daily intake (RDI) for these metals. While in Cucurbita moschata it ranges from 1.09% (Cr) to 5.47% (Cd). Conclusion: This study shows the contribution of non-essential elements (As, Pb, Cd and Cr) is high than essential elements (Fe and Zn). The HQ of Amaranthus sp ranges from 0.298 (Fe) to 9.930 (As) where about 67% of the analyzed metals have HQ > 1, reveals probable adverse health effects. In cucurbita sp the HQ ranges from 0.383 (Fe) to 4.41 (As). For the heavy metals analyzed the trend for HQ via ingestion, were observed that 50% of the analyzed metals have HQ > 1. Though, vegetable intake is just a proportion of food consumed, supplementary or complementary food that may include fish, rice and tobacco that are consumed can also contribute and/ increase amounts of heavy metals. Novelty: This study is beneficial to the individuals around the mine sites dealing with mineral materials associated with heavy metal contamination that affects their health through vegetable ingestion.